Vitamin D supplementation in a post-pandemic era: A narrative review - Pheagane G. Bopape; Chrisna Wagenaar; Madan Poka; Elmien Bronkhorst (South African Family Practice, 2023)
Vitamin D is a fat-soluble molecule referring to the different isoforms, ergocalciferol (D2) and cholecalciferol (D3). Its physiological functions include increasing calcium serum concentrations. 25-hydroxyvitamin D3 (25(OH)D) (Calcifediol), a non-active, circulating instant precursor is seen as a pre-hormone. Studies have shown that a deficiency in calcifediol is related to chronic conditions such as cardiovascular, musculoskeletal, immune system, neurological, and anti-neoplastic functions. Vitamin D supplementation has shown its benefit as prophylaxis and treatment during the coronavirus disease 2019 (COVID-19) pandemic and an increase in the prescribing of vitamin D supplementation has been observed. The intention of this review article is to provide guidance on the recommended dosage regimen as a prophylactic measure during COVID-19 and its use as a supplement in general. From this review article, it is clear that vitamin D has an important role to play not only in COVID-19 but also in various other health aspects of the human body.